EFFECTS OF CHROMIUM STRESS ON SEED GERMINATION AND EARLY SEEDLING GROWTH PERFORMANCES OF PEARL MILLET PENNISETUM GLAUCUM (L.) R. BR. (POACEAE) - Muhammad Zafar IQBAL; Sana MURTAZA; Muhammad SHAFIQ (Journal of Plant Development, 2023)
Heavy metals are widely available in the environment due to the natural processes, industrial, anthropogenic activities and ultimately in the results contaminate the immediate environment. The presence of the heavy metals such as Pb, Cd, Cr, Ni, Fe and Cu in environment disturb the quality of ecosystems, soils, water, air and vegetation. The chromium metal at higher level in ecosystem is an alarming signal for both developed and developing countries. Pennisetum glaucum is an annual grass which is widely cultivated in drought, rain fed and high temperature areas. The limited amount of literature available on the impact of chromium stress on P. glaucum. This study was conducted to investigate the beneficial or harmful effect of chromium stress on seed germination and seedling growth performances of P. glaucum in in vitro conditions. The different concentration of chromium 0, 25, 50, 75 and 100 ppm was applied. In present study, the overall results suggests the variable response on the rate of seed germination percentage and plant growth of P. glaucum to chromium stress was recorded. Results showed that the chromium treatment at 25 ppm significantly (p<0.05) reduced root growth of P. glaucum. The chromium at 50 ppm level significantly decreased the rate of percentage of seed germination of P. glaucum. The seedling dry weight of P. glaucum seedling was decreased highly at 75 ppm chromium. Root / shoot ratio also decreased due to gradual increase in chromium from low (25 ppm) to higher (100 ppm) levels. Similarly, the chromium at 25 to 100 ppm gradually decreased the percentage of tolerance and seedling vigor index of P. glaucum. An effective efforts for minimize the chromium toxicity and tolerance in plants are required.